Islamic Bank Governance During Pandemic Covid-19: A Systematic Literature Review - Nazaruddin Malik (Falah: Jurnal Ekonomi Syariah, 2022)
This study intends to categorize dominant topics related to Islamic bank governance and covid-19. This study was a systematic literature review using the Scopus database, from August 2020 to January 2021, as the main reference source to consider that this database have a high reputation in the international scientific field. The steps of study was carried out by summarizing various previous studies in order to find strategies and various problems related to Islamic Bank Governance during the Covid-19 pandemic. The Study found that there were three dominant topics related to Islamic bank governance and covid-19 as follows: development, profitability and covid-19. In addition, studies on this theme are also massively discussed based on several other dominant concepts such as Islamic banking, increase, financial performance, human capital efficiency, company and relationship. This study will contribute to enrich the Islamic bank’s resilience towards the negative impact of covid-19 in the future.